Nekatere etične dileme in vprašanja biotehnološkega razvoja v Evropi - Groboljšek, Blanka (Družboslovne razprave, 2011)
The article deals with some ethical and social aspects of the development of biotechnology which involves a complex area of scientific research and opens up a series of issues like how to define these aspects and how to include them in decision-making processes. Public discussions of biotechnology are often surrounded by dilemmas concerning the safety of GM organisms for people and the environment, the question of whether the public is sufficiently informed, the labelling of GM products and ethical and moral considerations regarding the process of genetic modification and therefore the main part of the article focuses on these issues. Namely, these issues call for a consideration of the new forms of interactions between science and society and open the path to different forms of political interventions and possibilities of shaping common European values in response to the ethical dilemmas of biotechnology development.
Keywords: Sociologija znanosti; Sociology of science; Biotechnology; Biotehnologija; Gensko spremenjeni organizmi; Transgenic organisms; Javnost; Public; Ethical aspects; Etični vidik; razvoj; družbeni nadzor; ethics; etika